Nutritional preconditioning induced by astragaloside Ⅳ on isolated hearts and cardiomyocytes against myocardial ischemia injury via improving Bcl-2-mediated mitochondrial function. (25th August 2019) - Luo, Yong; Wan, Qing; Xu, Min; Zhou, Qing; Chen, Xuepiao; Yin, Dong; He, Huan; He, Ming
Abstract: Ischemic preconditioning and pharmacological preconditioning are common strategies to prevent lethal myocardial injury, especially nutritional preconditioning (NPC). In this study, we investigated the effects of astragaloside IV (Ast), as an NPC agent, on myocardium suffered anoxia/reoxygenation (A/R) injury. Rats received 5 mg/kg Ast daily for 3 weeks by intragastric administration. Then, hearts were harvested and underwent A/R treatment using a Langendorff apparatus. Ast- pretreatment significantly promoted functional recovery of the myocardium, reduced infarct size, and oxidative stress, and decreased the apoptotic index. Similar findings were demonstrated in H9c2 cardiomyocytes that were pretreated with Ast for 24 h. Moreover, Ast-pretreatment significantly upregulated Bcl-2 expression, especially in mitochondria. The effects of Ast treatment against A/R injury were also reflected by increased antioxidant potential, inhibited reactive oxygen species (ROS) burst, increased oxygen consumption rate, maintained mitochondrial membrane potential (MMP), inhibited mitochondrial permeability transition pore (mPTP) opening, and prevented apoptosis. Selective inhibition of Bcl-2 by ABT-737 decreased myocardial injury protection of Ast. Ast-pretreatment resulted in NPC- related effects against A/R, and mitochondria may be the target of a cascade of events elicited by upregulating Bcl-2 expression, promoting translocation of Bcl-2 into mitochondria, maintaining MMP, inhibiting ROS bursts, thereby leading to recovery of mitochondrial respiration, preventing mPTP opening, decreasing cytochrome C release, preventing apoptosis, and ultimately alleviating myocardial injury. Graphical abstract: Image 1 Highlights: Astragaloside IV(Ast) is a nutritional preconditioning(NPC) agent. Small dosages and long-term oral Ast exerts cardioprotection against A/R injury. NPC induced by Ast is elicited by upregulating Bcl-2 expression. Mitochondria may be the target of NPC induced by Ast